Harnessing Cognitive Behavior Therapy and Thought Stopping Techniques: Transformative Group Counseling to Combat Sexual Violence among Inmates - Khofifah, Nur; Karneli , Yeni (Journal of Educational, Health and Community Psychology, 2025)
Sexual violence is a social phenomenon that remains widespread in Indonesia, involving not only adults but also children, both as victims and perpetrators. One form of sexual violence includes physical actions such as kissing, touching, and penetration, which stem from negative thoughts. Interventions are needed to address this behavior, one of which is group counseling based on Cognitive Behavior Therapy (CBT) with the thought stopping technique. This study aims to examine the effectiveness of group counseling using CBT with the thought stopping technique in reducing sexual violence behavior among inmates. The research employs a quantitative approach with a quasi-experimental design. The sample consists of 10 inmates in the experimental group and 10 in the control group, selected using purposive sampling. The instrument used is a questionnaire with a Likert scale, and data were analyzed using the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov Two Independent Samples, supported by SPSS version 26.0. The results show that: (1) the experimental group experienced a significant reduction in sexual violence behavior, reaching a low category; (2) the control group remained in the moderate category; (3) there were significant differences before and after the intervention between the experimental and control groups. Group counseling using CBT with the thought stopping technique is proven effective and can serve as an alternative intervention to address sexual violence.